Centralne sile ter vstop Italije v prvo svetovno vojno - Grafenauer, Danijel (Acta Histriae, 2017)
The appraisal of the reasons and consequences of the entry of Italy into the World War One was already dealt with from the historiographic point of view and the conclusions are more or less clear today. The views, analyses and interpretations in the past and partly also today depend on the origin of the "research approach". While in Vienna there was talk of treason, Rome talked about "national interests". Serious historians nowadays no longer use the word treason when discussing Italy's decisions in the years 1914-1915. Austrian and German historiography mentions the unfair Italian foreign policy, and both, so Italian as the Austrian and German researchers are convinced about the political hazard of the Italian state. It is interesting to follow the diplomatic activity, "obedience" and negotiations between Rome and Vienna from December 1914 to April and May 1915 as they disclose the whole "high" politics in the time of emergency state, i. e. wars and negotiations between them. In such times law and justice are in the background, with interests, power and alliances being in the focus. All this and no less is refl ected in the events taking place in these turbulent times between Austro-Hungary and Italy. It is necessary to add that regarding World War One Slovene historiography was mostly focused on the Slovene nation and its destiny, observing history through the national spectacles. That is why there is no Slovene historiographic literature on this topic. The present article is therefore a small stone in the mosaic of understanding the diversity of interests and events in the end of 1914 and beginning of 1915 until Italy's entry into war.
Keywords: Austria-Hungary; Avstro-Ogrska; Falkenhayn, Erich von; general; general officer; Germany; Hötzendorf, Conrad von; Italija; Italy; Nemčija; prva svetovna vojna; World War I